Masonry spandrels reinforced by thin-steel stripes: Experimental program on reduced-scale specimens. (1st November 2021) - Sandoli, A.; Pacella, G.; Lignola, G.P.; Calderoni, B.; Prota, A.
Highlights: Experimental program on monotonic behavior of masonry spandrels reinforced by thin-steel stripes. Seventeen tests on H -shaped scaled specimens. Effect of different slenderness ratios on monotonic behavior. Effect of different strengthening configurations to prevent brittle failure mechanisms. Analysis of the benefits provided by steel stripes reinforcement on strength, stiffness and ductility. Abstract: This paper presents the results of an experimental program conducted on H -shaped reduced-scale reinforced masonry spandrels subjected to monotonic loadings. It summarized tests units, test set-up and experimental results relative to seventeen samples reinforced by thin-steel stripes arranged with different configurations, and compared with those unreinforced. The first configuration comprised masonry spandrels strengthened by unbonded horizontal and diagonal steel stripes (i.e., stripes connected by means of threaded rods to the nodal area of the panel), while the second masonry spandrels reinforced by bonded horizontal stripes (i.e., stripes connected with 5 or 13 threaded rods over the spandrel length). For each reinforcement configuration, slender, intermediate and squat slenderness ratios have been considered for the samples. The conducted research investigated the effectiveness of the reinforcement to enhance the seismic response of the spandrels. Test results demonstrated that the application of steel stripes is beneficial in changing the failure modes from shear-dominated into flexural-dominated, especially for intermediate and squat panels prone to brittle shear mechanisms. Despite that increases of strength are reduced with respect to unreinforced samples, when reinforced the post-peak response changes significantly being it characterized by a remarkable ductile response for whatever spandrels' slenderness ratios.